Failure of homologous synapsis and sex-specific reproduction problems - Kurahashi, Hiroki; Kogo, Hiroshi; Tsutsumi, Makiko; Inagaki, Hidehito; Ohye, Tamae (Frontiers in Genetics, 2012)
The prophase of meiosis I ensures the correct segregation of chromosomes to each daughter cell. This includes the pairing, synapsis and recombination of homologous chromosomes. A subset of chromosomal abnormalities, including translocation and inversion, disturbs these processes, resulting in the failure to complete synapsis. This activates the meiotic pachytene checkpoint, and the gametes are fated to undergo cell cycle arrest and subsequent apoptosis. Spermatogenic cells appear to be more vulnerable to the pachytene checkpoint, and male carriers of chromosomal abnormalities are more susceptible to infertility. In contrast, oocytes tend to bypass the checkpoint and instead generate other problems, such as chromosome imbalance that often leads to recurrent pregnancy loss in female carriers. Recent advances in genetic manipulation technologies have increased our knowledge about the pachytene checkpoint and surveillance systems that detect chromosomal synapsis. This review focuses on the consequences of synapsis failure in humans and provides an overview of the mechanisms involved. We also discuss the sexual dimorphism of the involved pathways that leads to the differences in reproductive outcomes between males and females.